2020
DOI: 10.3390/biom10091344
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine (5-HT) Positively Regulates Pigmentation via Inducing Melanoblast Specification and Melanin Synthesis in Zebrafish Embryos

Abstract: It has been reported that 5-hydroxytryptamine (5-HT) is related to melanogenesis in mice and melanoma cells. However, the underlying mechanisms of 5-HT in regulating pigmentation remains unknown. In this study, we aim to clarify the regulatory mechanism of 5-HT in the pigmentation of zebrafish embryos and B16F10 cells. Our results show that 5-HT induces the pigmentation of zebrafish embryos in a dosage-dependent manner at concentrations of 0.01–1 mM. Whole mount in situ hybridizations and qRT-PCR in zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that 5-HT could promote the development of melanocytes in zebrafish embryos and the function of melanin synthesis in cultured melanocytes [ 21 ]. In this study, we confirmed the regulation of melanocyte function by 5-HT through adding excess 5-HT into the B16F10 melanoma cell line (in vitro) and PTU-treated zebrafish embryos (in vivo); α-MSH was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that 5-HT could promote the development of melanocytes in zebrafish embryos and the function of melanin synthesis in cultured melanocytes [ 21 ]. In this study, we confirmed the regulation of melanocyte function by 5-HT through adding excess 5-HT into the B16F10 melanoma cell line (in vitro) and PTU-treated zebrafish embryos (in vivo); α-MSH was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore (Figure 5), while many chemical inducers of pigmentation in zebrafish appear non-toxic in the short term (Karunarathne et al, 2019;Lv et al, 2020a;Liu et al, 2020;Molagoda et al, 2020;Ding Q. et al, 2021;Hong et al, 2022), comprehensive evaluations of long-term and acute toxicities remain scarce. Such assessments are paramount for the zebrafish model's broader application in therapeutic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5-HT was found to increase the expression of regeneration-associated genes, including kita, mitfa, and DCT34. These suggest that 5-HT may specifically activate the PKA/p-CREB signaling pathway, thereby up-regulating the expression of MITF and TYR to promote synthesis of melanin (Liu et al, 2020). Recent research has further elucidated the role of the 5-HT receptor in melanogenesis, showing that it enhances the pigmentation response to environmental stressors through the cAMP-PKA-MAPK, Rab27a/RhoA, and PI3K/AKT signaling pathways (Tang et al, 2023).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The primers used for RT‐PCR are listed in Table S1. The procedure of the whole‐mount in situ hybridization was followed as a previous report 31 . After hybridization, each embryo was photographed under a dissecting microscope using a digital camera.…”
Section: Methodsmentioning
confidence: 99%